HIGH-TECH MEDICAL CARE TO RESTORE BLOOD FLOW IN PATIENTS WITH RESTENOSIS (World Bulletin of Public Health, 2023)
The purpose of the study is to justification of the choice of a surgical method for the treatment of restenosis
Keywords: percutaneous intervention; stenting; restenosis